2018
DOI: 10.1007/s10661-018-6600-z
|View full text |Cite
|
Sign up to set email alerts
|

The impact of industrial wastewater on the physicochemical and microbiological characteristics of groundwater in Ajao- Estate Lagos, Nigeria

Abstract: In Ajao Estate, it is believed that poor quality of its groundwater is unconnected to the dislodging of wastewater into the environment by food- and wine-producing industries operating in the area. To ascertain this claim, the impact of this wastewater on microbiological and physicochemical quality of the groundwater was evaluated. Microbiological result of water samples revealed decrease in Staphylococcus aureus, Clostridium spp., Escherichia coli, etc. count from the industrial wastewater dislodging point. G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…I-geo was calculated using the concentration of the following physicochemical parameters from the top layer of both soils pH, PAH, THC, TPHC, TOC, O&G, Cr, Fe, Ni, Pb and Cu using DPR ( 2002) permissible limit as the background value (Table 4). I-geo classification scheme adopted by Muller (1969) and Ukah et al (2018) showed pH, Cr, Fe, Ni, Pb and Cu in the active site to be unpolluted since I-geo values are less than 1 (Fig. 3).…”
Section: Geo-accumulation Index (I-geo)mentioning
confidence: 99%
“…I-geo was calculated using the concentration of the following physicochemical parameters from the top layer of both soils pH, PAH, THC, TPHC, TOC, O&G, Cr, Fe, Ni, Pb and Cu using DPR ( 2002) permissible limit as the background value (Table 4). I-geo classification scheme adopted by Muller (1969) and Ukah et al (2018) showed pH, Cr, Fe, Ni, Pb and Cu in the active site to be unpolluted since I-geo values are less than 1 (Fig. 3).…”
Section: Geo-accumulation Index (I-geo)mentioning
confidence: 99%
“…Notwithstanding, the increased THMs accumulation in (edible) organs owed to goat s feeding habit and anthropogenic activities, the chevon remains increasingly relished as a special delicacy in Nigeria. Thus, the indiscriminate anthropogenic activities that result in environmental contamination, and subsequent accumulation of THMs [37,38] makes the detection and quantification of toxic metals in goat carcasses processed for human consumption in Nigeria imperative. The work by Okoye and Ugwu [39], to our best knowledge, appears to be the only recent report on toxic metal contamination of goat muscles and edible offals, which was specific to the South-Eastern region of Nigeria, and this was conducted over a decade ago.…”
Section: Introductionmentioning
confidence: 99%
“…Lithologically, Oshodi is underlain by two different lithologicunit; the coastal plain sand and the alluvial river sand. Both sands are part of Dahomey Basin [13]. Coastal plain sand is the aquifer in the study area though very shallow in general [13].…”
Section: Methodsmentioning
confidence: 94%
“…Both sands are part of Dahomey Basin [13]. Coastal plain sand is the aquifer in the study area though very shallow in general [13].…”
Section: Methodsmentioning
confidence: 94%